Integrating geothermal energy and desalination unit into a poly-generation configuration: Comprehensive study and optimization - Hai, Tao; Chaturvedi, Rishabh; Almujibah, Hamad; Marjan, Riyam K.; Thuong, T. Van; Soliman, N.; El-Shafai, W.; Fouad, H. (ELSEVIER, 2024)
The recent reviews that have been conducted serve to highlight the remarkable effectiveness that can be achieved by combining various technologies to extract energy efficiently from underground reservoirs. In this particular study, our focus is on a geothermal-driven poly-generation plant that ingeniously integrates a single flash binary geothermal power unit with multiple sub-systems. In order to comprehensively evaluate environmental impacts, we have conducted extended-environmental and exergo-environmental assessments, which have allowed us to calculate CO2 emissions levels as well as the sustainability index. Through bi-objective optimization, the optimal operational conditions can be determined in this system. The investigation of dead temperature reveals the most significant changes in energy and exergy efficiencies, as well as in the CO2 emission rate. A notable conflict arises between exergy efficiency and the system product cost, making it essential to consider both as objectives in optimization efforts. Under optimal conditions, the total input exergy is 1043 kW. However, the system still experiences an exergy destruction rate of 484.1 kW. The highest rate of exergy destruction is observed in the vapor generator of the organic flash cycle, which accounts for 130.7 kW.
Keywords: CO 2 emission rate; Exergo-environmental assessment; Bi-objective optimization; Renewable energy; Poly-generation system; FLASH CYCLE OFC; POWER-PLANT; EXERGOECONOMIC ANALYSIS; ORGANIC-FLASH; WASTE HEAT; MULTIOBJECTIVE OPTIMIZATION; MULTIGENERATION SYSTEM; THERMODYNAMIC ANALYSIS; TRIGENERATION SYSTEM; GENETIC ALGORITHM; Engineering; Water Resources